GÜNÜMÜZ TÜRKİYE KOPUZ'UNDAKİ ORGANOLOJİK VE İCRASAL ÖZELLİKLERİN DEĞERLENDİRİLMESİ - GERÇEK, ÖNER (Fırat Üniveristesi, 2015)
Asya ve Anadolu müzik geleneğinde köklü bir geçmişe sahip olan kopuz, yaylı ve yaysız sazların atası, kendisine doğaüstü güçler atfedilen kutsal bir saz olmuştur. Bundan dolayı farklı yapıda ve farklı çalınış biçimindeki birçok çalgının ortak ismidir. Bugün ise kopuz, farklı akort sistemleri, yapısal gelişmeler ve bu konuda elde edilen deneyimler ışığında farklı icra teknikleriyle Anadolu müziğinde kendine özgü tınısıyla varlık gösteren; önemle üzerinde durulması ve sahiplenilmesi gereken bir saz olma özelliğini devam ettirmektedir. Günümüz ile günümüz öncesi kopuzun yapı ve icra mukayesesi başlığı altında herhangi bir kitap ve makalenin yazılmamış olması bu konu ile ilgili bu çalışmanın yapılmasını zorunlu kılmaktadır. Çalışmamızda kopuzda meydana gelen köklü değişikler ele alınmış, günümüz öncesi ve günümüz kopuzu arasındaki yapısal ve icrasal farklılıklar ele alınarak mukayese yapılmıştır. İcra tekniğinde ise diğer enstrümanlarda kullanılan tekniklerin kullanılması ve farklı akort sistemlerinin bulunması ve geliştirilmesi çalışmamızın başlıca konularındandır. Anahtar Kelimeler: Kopuz, Şelpe , Pençe, Bağlama, Çalgı

The Kopuz which has a rich heritage in the musical tradition of Asia and Anatolia has been a sacred instrument that various supernatural powers were attributed to itself regarded as the predecessor of stringed instruments played with or without bows. For this reason,the Kopuz is the common name of various instruments played in different structure and various playing techniques. Currently the Kopuz with its different chord systems, structural improvements, and various playing techniques based on experiences drawn from certain developments, has a place in Anatolian music with its unique tone and therefore maintains its importance of being a characteristic instrument that deserves a special interest. Owing to the fact that, there is not any book or article published in relation with comparison of the structure and performance of contemporary and early Kopuz, it has become a compelling case to make this research. İn this study, the most important fundamental changes the Kopuz underwent in history has been evaluated. In addition to that, structural and performing differences of present and early Kopuz have been compared and discussed diligently. By means of performance, the use of playing techniques seen in other instruments and the innovation and improvement of different chord systems will be the primary focus of this study. Keyword: Kopuz, Şelpe, Pençe, Baglama, Instrument
Evaluation of the organologic and performing characteristics of today's kopuz in Turkey
Keywords: Müzik